A lasting bond: on a transferred death ritual from ancient Cynopolis - Arbeloa Borbon, Paula (SPAL - Revista de Prehistoria y Arqueología, 2023)
This paper seeks to analyse two groups of reddish wax magic figurines discovered in the cemetery of the ancient city of Cynopolis and preserved at the Antiquities Museum of the Bibliotheca Alexandrina, with the aim of offering a critical and updated exegesis of these exceptional magical artefacts from Roman Egypt. By analysing features including material, colour, morphology and iconography, and by examining the effigies alongside parallel rituals, I argue that this ensemble should be best understood as a ‘transferred death ritual’, whose aim was to ensure an effective death and the sending of the deceased to the underworld.